Magnetic nanoparticles for eliminating endocrine-disrupting compounds in water treatment – a quantitative systematic analysis - Guimarães, Juliana; Taveira, Igor; Anacleto, Thuane Mendes; Enrich-Prast, Alex; Abreu, Fernanda (Frontiers in Environmental Science, 2024)
Endocrine-disrupting compounds (EDCs) are a group of emergent pollutants that affect the endocrine system. EDCs can cause harm to humans and animals and unbalance the aquatic ecosystem even at low concentrations. Several methods are applied to remove EDCs, and recently, magnetic nanoparticles (MNPs), a low-cost and magnetically-responsive approach, have been introduced as modern innovative tools for this purpose. Thus, we conducted a systematic analysis to determine the characteristics of MNPs required to optimize EDCs removal in water/waste treatments. Most studies used magnetite (Fe3O4) nanoparticles, a low-cost and easily acquired material, followed by other metallic oxides nanoparticles (MOPs) like zinc, copper, and nickel oxides. Short adsorption time (0.5–15 min) and small MNP (10–80 nm) were the most prominent and successful in EDCs recovery approaches. After analyzing data published in the last decade, results showed that, in general, processes that apply lower concentrations of MNP seem to achieve a significant higher removal rate. For instance, MNPs formulations are able to successfully remove >90% of bisphenols and phthalates. However, depending on the EDCs type, the concentration of MNPs have to be adjusted to increase EDCs recovery rates, possibly due to their different chemical compositions and properties. Our results indicate that MNPs are an efficient, with potential to be a relatively cheap way to extract or eliminate EDCs from wastewater and should be considered an innovative tool to be included in waste treatment protocols.